URGENSI MEDIA DALAM PENINGKATAN KUALITAS PEMBELAJARAN - ABBAS, Abbas (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2016)
Abstract: Media is a determinant factor to the success of learning process because it facilitates the instructional objective achievement. This assumption can be understood because the use of media in the learning process may stimulate the learners’ motivation and understanding towards presented materials. To select media, there are some points that must be considered like the targeted instructional objective, the learners’ characteristics, the learning construction, and so forth. By implementing media in the leraning process as well as considering many factors associating with the media in the learning process, the learning quality will be increased. Kata Kunci: Media dan Kualitas Pembelajaran